Formalizacja wiedzy prawnej metodą VTKB - analiza możliwości - Mach, Maria Antonina (Formalisation of Legal Knowledge with the VTKB Method - Analysis Of Method's Abilities, 2006)
The paper deals with the problem of formalising changes of a knowledge base that contains legal statements. It shows the significance of legal knowledge (including knowledge concerning legal barriers to entry) for the process of formulating enterprise's strategy. The main part of the paper is devoted to the analysis of different versions of the VTKB method of formalising legal knowledge base's evolution, in the context of reasoning about legal barriers to entry.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 93-104